Migration from Mexico to the United States: wage benefits of crossing the border and going to the U.S. interior - Aguayo Téllez, Ernesto; Rivera Mendoza, Crhistian I. (Wiley-Blackwell, 2011)
Abstract Emigrating from Mexico to the United States requires three steps: going to the border, crossing it, and going to the final U.S. destination. This article attempts to measure the earnings benefits of each migration step, focusing particularly on the second step: crossing the border. Using U.S and Mexican microdata of workers living in Mexico and in the United States, this article compares wages of identical individuals on both sides of the border after controlling for unobserved differences between migrants and nonmigrants. On average, Mexican workers increase their wages 1.22 times by moving to the Mexican side of the border, 4.15 times by crossing it, and 1.12 times by moving to an interior location in the United States. Gains are larger for unskilled workers. Also, gains for crossing the border are larger for illegal workers, while gains for going to the U.S. interior are larger for legal workers.